Thyroid Autoimmunity in Female Infertility and Assisted Reproductive Technology Outcome - Bucci, Ines; Giuliani, Cesidio; Di Dalmazi, Giulia; Formoso, Gloria; Napolitano, Giorgio (Frontiers in Endocrinology, 2022)
The regulation of the female reproductive system is one of the most relevant actions of thyroid hormones. Adequate thyroid hormones production is essential for normal menstrual function and fertility as well as for the successful maintenance of pregnancy. The relationship between reproductive failure and thyroid disorders is particularly relevant and attracts attention worldwide. Thyroid autoimmunity (TAI), defined by the presence of circulating antithyroid antibodies targeting thyroid peroxidase (TPOAb) and thyroglobulin (TgAb), is prevalent among women of reproductive age and is the most frequent cause of thyroid dysfunction. Several studies addressed the association between TAI, thyroid function, and fertility as well as pregnancy outcome after spontaneous or assisted conception. Infertility, miscarriages, and fetal-maternal complications are described in overt autoimmune hypothyroidism. More debatable is the role of mild thyroid dysfunction, mainly subclinical hypothyroidism (SCH), and TAI in the absence of thyroid dysfunction in infertility and reproductive outcome. Assisted reproductive technology (ART) has become an integral element of care for infertility. Women with TAI undergoing ART are of particular interest since they carry a higher risk of developing hypothyroidism after the ovarian stimulation but whether TAI, in absence of thyroid dysfunction, adversely affects ART outcome is still controversial. Likewise, the role of levothyroxine (LT4) in improving fertility and the success of ART in euthyroid women with TAI is unclear. This review discusses the role of TAI, in the absence of thyroid dysfunction, in infertility and in ART outcome.